Pengaruh Daerah Tempat Tumbuh Terhadap Kadar Kafein Biji Kopi Robusta (Coffea canephora) - Mega Putri (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Coffee is one of the plantation commodities with high economic value and an important role as a source of foreign exchange for the country. One type of coffee that is commonly cultivated in Indonesia is Robusta coffee. Robusta coffee (Coffea canephora L.) is known to have higher caffeine than Arabica coffee, so the stimulant effect given by Robusta coffee will be greater than Abarica coffee. The content of secondary metabolites including caffeine, in coffee, is strongly influenced by environmental factors, such as the altitude where it is grown. The purpose of this study was to determine the difference in the place of growth (height) to the caffeine content in coffee beans. The coffee bean powder was extracted with distilled water and the extracted liquid-liquid with chloroform to produce a caffeine fraction. The caffeine fraction, which has been evaporated with the solvent, was then analyzed qualitatively with parry reagents and quantitatively with UV spectrophotometry. The caffeine content in coffee samples and analyzed using SPSS software. The results of the qualitative test using parry reagent proved that all samples of robusta coffee, namely Merapi, Menoreh, Turgo, and Temanggung contained caffeine which was marked in green. The quantitative test stated that the highest caffeine content was coffee beans originating from Merapi with a level of 1,85%.